Sedimentary ancient DNA from the subarctic North Pacific - Zimmermann, Heike (Dr.); Stoof-Leichsenring, Kathleen R. (Dr.); Kruse, Stefan (Dr.); Nürnberg, Dirk (Prof. Dr.); Tiedemann, Ralf (Prof. Dr.); Herzschuh, Ulrike (Prof. Dr.) (Paleoceanography and Paleoclimatology, 2021)
We traced diatom composition and diversity through time using diatom-derived sedimentary ancient DNA (sedaDNA) from eastern continental slope sediments off Kamchatka (North Pacific) by applying a short, diatom-specific marker on 63 samples in a DNA metabarcoding approach. The sequences were assigned to diatoms that are common in the area and characteristic of cold water. SedaDNA allowed us to observe shifts of potential lineages from species of the genus Chaetoceros that can be related to different climatic phases, suggesting that pre-adapted ecotypes might have played a role in the long-term success of species in areas of changing environmental conditions. These sedaDNA results complement our understanding of the long-term history of diatom assemblages and their general relationship to environmental conditions of the past. Sea-ice diatoms (Pauliella taeniata [Grunow] Round & Basson, Attheya septentrionalis [ostrup] R. M. Crawford and Nitzschia frigida [Grunow]) detected during the late glacial and Younger Dryas are in agreement with previous sea-ice reconstructions. A positive correlation between pennate diatom richness and the sea-ice proxy IP25 suggests that sea ice fosters pennate diatom richness, whereas a negative correlation with June insolation and temperature points to unfavorable conditions during the Holocene. A sharp increase in proportions of freshwater diatoms at similar to 11.1 cal kyr BP implies the influence of terrestrial runoff and coincides with the loss of 42% of diatom sequence variants. We assume that reduced salinity at this time stabilized vertical stratification which limited the replenishment of nutrients in the euphotic zone.